2014
DOI: 10.1007/s10585-014-9648-3
|View full text |Cite
|
Sign up to set email alerts
|

Features and prognostic impact of distant metastasis in patients with stage IV lung adenocarcinoma harboring EGFR mutations: importance of bone metastasis

Abstract: Mutated epidermal growth factor receptor (EGFR) and signaling pathways were associated with multiple brain and intra-pulmonary metastases, oncogenic progression and metastasis. However, features of metastasis to other organs and the independent prognostic influence of metastatic lesions were not elucidated in patients with lung cancer harboring EGFR mutations. Between January 2007 and April 2012, we treated 277 patients diagnosed with stage IV lung adenocarcinoma. Studied were 246 patients with available tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 39 publications
4
43
2
Order By: Relevance
“…To the best of our knowledge, this is the first study to assess the association between bone metastasis and a poorer PFS time in EGFR mutation-positive NSCLC patients. In a previous report, Fujimoto et al (15) revealed that bone metastasis was a significant independent negative predictive factor for OS time in EGFR mutation-positive patients. By contrast, in the present study, bone metastasis was not associated with OS time.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first study to assess the association between bone metastasis and a poorer PFS time in EGFR mutation-positive NSCLC patients. In a previous report, Fujimoto et al (15) revealed that bone metastasis was a significant independent negative predictive factor for OS time in EGFR mutation-positive patients. By contrast, in the present study, bone metastasis was not associated with OS time.…”
Section: Discussionmentioning
confidence: 93%
“…The toxicities of EGFR-TKIs are decreased compared with those of cytotoxic drugs and patients can achieve a good quality of life while using them (8,12). In patients treated with first generation EGFR-TKIs, brain, bone and liver metastasis and pleural effusion (PE) predicted a poorer prognosis compared with patients without these metastasis (13)(14)(15)(16)(17). However, few reports concern the association between the site of metastasis and prognosis (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…The NOS was used to perform quality assessment on all 22 studies and 14 (17,18,(25)(26)(27)(28)30,(32)(33)(34)(35)(36)38,42) high-quality and 8 (16,19,29,31,37,(39)(40)(41) as low-quality.…”
Section: Study Description and Quality Assessmentmentioning
confidence: 99%
“…The presence of bone metastases is associated with poor prognosis in some cancers, such as lung adenocarcinoma, gastric adenocarcinoma, hepatocellular carcinoma and ovarian carcinoma [16,17,18,19,20]. In a large series of 360 patients with MESCC, 7% were found to have bone metastases, against 16 and 13% in both of our cohorts [21].…”
Section: Discussionmentioning
confidence: 89%